Tumour sink effect on 68Ga-PMSA PET/CT: A case of diffuse metastatic disease of prostate cancer - Sharjeel Usmani; Khulood Al Riyami; Sofiullah Abubakar; Anjali Jain; Asiya Al Busaidi (Journal of the Pakistan Medical Association, 2023)
68Ga-PMSA imaging has revolutionized both diagnosis and radioligand therapy selection in patients with metastatic prostate cancer. We report a case of a 59-year-old recently diagnosed prostate cancer with high PSA level pf >2000ng/ml referred for 68Ga-PSMA PET/CT. 68Ga-PSMA PET/CT showed diffuse intense tracer uptake throughout the axial and appendicular skeleton with significantly lower uptake of 68Ga-PSMA in normal organs in a configuration of “tumour sink effect”. Findings are in keeping with diffuse skeletal infiltration and suspected marrow infiltration. Given the extensive nature of bone disease and pattern, 177Lu-PSMA-targetted radioligand therapy was thought to be more appropriate in a given situation with a favourable toxicity profile. Keywords: 68Ga-PSMA PET/CT; tumor sink effect; 177Lu-PSMA-RLT; PET/CT